Non-Linear Characterization of Memoryless SSP Amplifiers - N. T. Ali (Active and Passive Electronic Components)
This paper describes a testbed, which is able to generate all of the standard test signals used for characterising nonlinear amplifiers. The testbed is shown to be sufficiently linear to avoid any possible masking of the non-linear effects of the amplifier under test. All the standard tests: single-carrier, two-carrier, multi-carrier and NPR are applied to a laboratory amplifier and their results found to be in reasonably good agreement with the most popular prediction techniques. The merits of the individual test have been highlighted.